2021
DOI: 10.17305/bjbms.2021.6299
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin ameliorates testosterone secretion disorder by inhibiting endoplasmic reticulum stress through the miR-1306-5p/HSD17B7 axis in diabetic rats

Abstract: Testicular damage and testosterone secretion disorder are associated with diabetes mellitus. Quercetin,  a common flavonoid, has antioxidant, anti-cancer,  and blood sugar lowering effects. Therefore, this study aims to investigate the effect of quercetin on the reproductive system of male rats with diabetes in vivo and in vitro and elucidate its mechanism. Streptozotocin (STZ)  induction was used to establish a diabetes model in forty male Sprague Dawley (SD) rats, which were subsequently administered with 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…In the meantime, the testicular weights were increased following QUE supplementation in both experimental groups. A similar phenomenon was reported by Khaki et al [27] and Wang et al [28] hypothesizing that QUE was able to improve the hypothalamic-pituitary-testicular function and ameliorate structural changes to the seminal epithelium caused by chronic hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…In the meantime, the testicular weights were increased following QUE supplementation in both experimental groups. A similar phenomenon was reported by Khaki et al [27] and Wang et al [28] hypothesizing that QUE was able to improve the hypothalamic-pituitary-testicular function and ameliorate structural changes to the seminal epithelium caused by chronic hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…Increased ROS levels activate the JAK2/NFκB pathway in the testis, which triggers apoptosis and results in dysfunctional testicles, while JAK2 inhibition reduces oxidative damage and cell apoptosis in the testis [21,22]. In vitro, JAK/STAT phosphorylation was increased in high glucose, and quercetin treated Sertoli cells, implicating JAK's role in diabetes-induced testicular damage [23]. Upon activation by JAK2, the roles of STAT1 and STAT3 in cell proliferation and apoptosis is still controversial, with some studies associating the two STATs with either function depending on the type of tissue and the nature of the injury [24].…”
Section: Discussionmentioning
confidence: 98%
“…The potential pharmacological effects of quercetin have been extensively explored as dietary constituents. Due to its antioxidative, anti-inflammatory, and anti-apoptotic effects, it has been clinically applied for the treatment of various diseases ( 11 15 ). In this study, we found that quercetin increased bone mass and improved bone strength in orchiectomy mice, indicating that quercetin has therapeutic effects on osteoporosis induced by testosterone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the testes, 95% of testosterone is produced, with the remaining 5% secreted by the adrenal glands. Recent research has shown that the main mechanism by which quercetin increases testosterone is by promoting its synthesis in the Leydig cells ( 15 ). Notably, quercetin significantly increased the serum levels of testosterone, OCN, and uOCN after orchiectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation